2022
DOI: 10.1101/2022.07.26.501658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental Stability of Enveloped Viruses is Impacted by the Initial Volume and Evaporation Kinetics of Droplets

Abstract: Efficient spread of respiratory viruses requires the virus to maintain infectivity in the environment. Environmental stability of viruses can be influenced by many factors, including temperature and humidity. Our study measured the impact of initial droplet volume (50, 5, and 1 µL) and relative humidity (RH: 40%, 65%, and 85%) on the stability of influenza A virus, bacteriophage, Phi6, a common surrogate for enveloped viruses, and SARS-CoV-2 under a limited set of conditions. Our data suggest that the drying t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…After this sharp decay, remaining infectious viral titers were stabilised, giving an inverted sigmoidal decay curve over the entire 60-minute time-course. This sigmoidal decay for IAV in droplets has been observed before (18,19), with the sharpest decline in infectious titers occurring just prior to droplet efflorescence, when the salt molality of the droplets is maximal.…”
Section: Resultssupporting
confidence: 67%
“…After this sharp decay, remaining infectious viral titers were stabilised, giving an inverted sigmoidal decay curve over the entire 60-minute time-course. This sigmoidal decay for IAV in droplets has been observed before (18,19), with the sharpest decline in infectious titers occurring just prior to droplet efflorescence, when the salt molality of the droplets is maximal.…”
Section: Resultssupporting
confidence: 67%
“…Similarly, Niazi et al 31,32 showed that rapid evaporation and hence rapid efflorescence stabilizes IAV and human rhinovirus-16 in airborne aerosol particles, suggesting that increased stability is due to a shorter exposure to high salinity. An important role of evaporation dynamics on IAV inactivation in droplets was also proposed by French et al, 23 who observed faster inactivation during the initial evaporation step, while the particle is still liquid, and a slower decay after efflorescence. Likewise, a near-instantaneous 50% loss in SARS-CoV-2 infectivity was observed to be associated with efflorescence, followed by a slower inactivation rate.…”
Section: Introductionmentioning
confidence: 52%
“…In typical indoor environments in temperate climates, RH can be as low as 30% during winter, whereas it is around 50% in summer. 8 The RH, [9][10][11][12][13][14][15][16][17][18][19] the temperature, [20][21][22] and the initial size and composition of the expiratory particle [23][24][25] dictate the droplet drying rate and hence the concentration of solutes in the droplets. If the RH is below the efflorescence relative humidity (ERH) of the salts, the salts will effloresce.…”
Section: Introductionmentioning
confidence: 99%
“…8−15 SARS-CoV-2 has been shown to decay faster in smaller droplets compared to larger ones (1 vs 50 μL) under some conditions. 18 Therefore, it is essential to examine the survival of SARS-CoV-2 deposited on masks in aerosolized form.…”
Section: ■ Introductionmentioning
confidence: 99%